A nonequal gap distance dielectric barrier discharge: Between spiral‐shaped and cylinder‐shaped electrodes. Issue 9 (9th May 2022) - Jin, Shaohui; Zhao, Feng; Nie, Lanlan; Liu, Dawei; Lu, Xinpei
Abstract: In this paper, a nonequal gap distance dielectric barrier discharge (DBD) between a spiral‐shaped electrode and a cylinder‐shaped electrode is reported. A spiral‐shaped plasma is generated when a nanosecond pulse voltage is applied to the two electrodes. The smaller the pitch of the spiral‐shaped electrode is, the more diffuse the plasma appears. The discharge current has a pulse width of more than 400 ns, which is much longer than that of ordinary DBDs in air. According to the high‐speed photographs of the plasma captured by an intensified charge‐coupled camera detector camera, the discharge first ignites at the position where the gap distance is smallest, then it propagates continuously along the spiral electrode with the increase of gap distance at a speed of about 106 m/s. Both the optical emission spectrum method and the electric field‐induced second harmonic method are employed for the measurement of the electric field at different locations. The obtained electric field from both methods have a good agreement and are in the range of 60–110 kV/cm depending on the gap distance of the locations, which is much higher than the breakdown voltage of air under direct current voltage. This structure can obtain diffuse plasma in a larger gap, which makes the application of DBD more extensive. And it also has a deeper understanding of DBD with nonequal gap distance. Abstract : In this paper, we proposed a nonequal gap distance dielectric barrier discharge (DBD) between a spiral‐shaped electrode and a cylinder‐shaped electrode. The homogeneous plasma can also be obtained in the larger gap distance. And the position of the plasma production is controllable according to the different pitches of the spiral‐shaped electrode. This is helpful to deepen the understanding of air DBD and expand its application.